Exploiting the Continuous in situ Generation of Mesyl Azide for Use in a Telescoped Process. Issue 44 (19th October 2017) - O'Mahony, Rosella M.; Lynch, Denis; Hayes, Hannah L. D.; Ní Thuama, Eilís; Donnellan, Philip; Jones, Roderick C.; Glennon, Brian; Collins, Stuart G.; Maguire, Anita R.
Abstract : The hazardous diazo transfer reagent mesyl azide has been safely generated and used in situ for continuous diazo transfer as part of an integrated synthetic process with an embedded safety quench. Diazo transfer to β‐keto esters and a β‐ketosulfone was successful. In‐line phase separation, by means of a continuous liquid–liquid separator, enabled direct telescoping with a thermal Wolff rearrangement. Abstract : The hazardous diazo transfer reagent mesyl azide has been safely generated and used in situ for continuous diazo transfer as part of an integrated synthetic process with an embedded safety quench. Diazo transfer to β‐keto esters and a β‐ketosulfone was successful. In‐line phase separation, by means of a continuous liquid–liquid separator enabled direct telescoping with a thermal Wolff rearrangement.